Balancing Public Trust and Legal Literacy: Assessing Community Readiness for Electronic Land Certificates within Digital Land Administration - Sri Widyawati (Journal Evidence Of Law, 2025)
The digitalization of land administration particularly through the implementation of Electronic Land Certificates constitutes a key component of Indonesia’s national land administration reform agenda. However, the success of this policy is not determined solely by technological readiness and regulatory frameworks, but also by the social and legal readiness of the community as the primary users of land services. This article aims to analyze community readiness for Electronic Land Certificates by examining the relationship between public trust and legal literacy. The study employs a descriptive-quantitative approach with interpretative analysis based on questionnaire data collected from residents of Duri Kepa Subdistrict who participated in a community service program organized by the Faculty of Law, Universitas Esa Unggul Jakarta, on 12 August 2025. The findings reveal a structural gap between high levels of public trust in land administration institutions and Land Deed Officials (PPAT) and low levels of procedural understanding regarding land registration, Electronic Land Certificates, and personal data protection risks. This gap indicates the emergence of trust-based compliance, in which acceptance of digital land services relies more on institutional legitimacy than on substantive legal understanding. The article argues that such compliance is inherently fragile and may undermine the sustainability of land administration digitalization if not accompanied by systematic legal education, a human-centered approach, and the strengthened role of Land Deed Officials (PPAT) as legal facilitators in the transition toward a digital land administration system.